Pulling Together or Pulling Apart? Perspectives on Nationhood, Identity, and Belonging in Europe - Bayó Belenguer, Susana; Brady, Nicola (Peter Lang International Academic Publishing Group, 2019)
In the aftermath of the twentieth century's raging warfare, attempts were made to create an environment in which new relationships between European nations could be built around a common identity. Yet, in the twenty-first century, identity conflicts are gaining a new intensity in parts of the continent. In the analysis of some sub-state nationalist parties, the prospect of European Union membership reduces the economic and political risks of secession. Meanwhile, to the east, any moves towards expansion of EU membership are viewed by Russia not as a peace project but as acts of aggression. This volume assembles a series of comparative and single-area case studies drawn from different academic disciplines.